2004
DOI: 10.1063/1.1845595
|View full text |Cite
|
Sign up to set email alerts
|

Generation of periodic microrelief in tensioned polymeric substrates with hard coating and their physical properties

Abstract: The effect of formation of a periodic surface microrelief upon tension of polymeric substrates with thin hard coatings under specified conditions (the processing temperature below the glassing temperature, elongation up to 250%, elongation rate <5mm∕min) is described. The microrelief period ranges from 0.5μm up to hundreds of micrometers, its height up to 1μm. Methods are proposed to measure low values of the optical path length in media Δn∼λ and azimuthal anchoring energy of a liquid crystal on microre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…9,10 Several groups have isolated the contributions that surface topography can make to azimuthal anchoring energies by studying LCs in contact with substrates having feature sizes that can be systematically controlled (e.g. surface gratings 11,12 or periodic microrelief structures prepared by the deformation of hard coatings supported on soft polymeric substrates 13 ). Distortion of the director of the LC over the topography of the surface can create an "elastic contribution" to the anchoring energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Several groups have isolated the contributions that surface topography can make to azimuthal anchoring energies by studying LCs in contact with substrates having feature sizes that can be systematically controlled (e.g. surface gratings 11,12 or periodic microrelief structures prepared by the deformation of hard coatings supported on soft polymeric substrates 13 ). Distortion of the director of the LC over the topography of the surface can create an "elastic contribution" to the anchoring energy.…”
Section: Introductionmentioning
confidence: 99%
“…A number of past studies have reported measurements of the azimuthal anchoring energy of mechanically sheared, polymeric surfaces. It is now understood that mechanical shearing of polymeric surfaces simultaneously introduces two elements of surface structure that can influence the anchoring energy of a LC: (1) micro- and nanogrooves (topography) and (2) preferred alignments of the polymer chains in the near-surface region of the substrate. , Several groups have isolated the contributions that surface topography can make to azimuthal anchoring energies by studying LCs in contact with substrates having feature sizes that can be systematically controlled (e.g. surface gratings , or periodic microrelief structures prepared by the deformation of hard coatings supported on soft polymeric substrates). Distortion of the director of the LC over the topography of the surface can create an “elastic contribution” to the anchoring energy .…”
Section: Introductionmentioning
confidence: 99%